Evidence of a non-progressive course of alternating hemiplegia of childhood: study of a large cohort of children and adults - Panagiotakaki, Eleni; Gobbi, Giuseppe; Neville, Brian; Ebinger, Friedrich; Campistol, Jaume; Nevšímalová, Soňa; Laan, Laura; Casaer, Paul; Spiel, Georg; Giannotta, Melania; Fons, Carmen; Ninan, Miriam; et al. (Brain, 2010)
Alternating hemiplegia of childhood is a neurological disorder characterized by episodes of hemiplegia, various non-epileptic paroxysmal events and global neurological impairment. Characterization of the evolution and outcome into adulthood has not been sufficiently investigated. The goal of this study was to elucidate the natural history of alternating hemiplegia within a large cohort of 157 patients, as part of the European Network for Research on Alternating Hemiplegia project. A questionnaire was formulated to determine the severity of both paroxysmal and global neurological impairment and address progression of the disorder by allocating data to specific age epochs up to and over 24 years of age. Patients in early age groups were consistently present in subsequent later age groups and for each patient, data were collected for each corresponding age epoch. The study was based on predominantly retrospective and, for a period of 2 years, prospective data. At inclusion, patients were aged from 9 months to 52 years. The median age at diagnosis was 20 months. All patients experienced hemiplegic attacks; 86.5% reported episodes of bilateral weakness, 88% dystonic attacks, 53% epileptic seizures, 72% developed chorea and/or dystonia and 92% mental retardation. When data over the course of the illness were examined for the whole cohort, the severity of symptoms did not appear to change, with the exception of abnormal ocular movements and hypotonia that regressed, but did not disappear into adulthood (from 86 to 36% and 76 to 36%, respectively). No statistically significant correlation between a history of severe paroxysmal hemiplegic/dystonic episodes and a worse neurological outcome was identified. Seven patients died, some of whom experienced severe plegic attacks or epileptic seizures at the time of death. History of severe plegic/dystonic attacks was not found to be an aggravating factor for deceased patients. Our results provide evidence that the natural history of alternating hemiplegia is highly variable and unpredictable for individual patients. However, we did not find evidence to support a steadily progressive and degenerative course of the disorder when patients were analysed as a group. For a minority of patients, a risk of sudden death was associated with more severe neurological impairment. The European Network for Research on Alternating Hemiplegia Registry, validated by our study, includes all major neurological signs and symptoms of alternating hemiplegia and may thus be used as a precedent for the progressive inclusion and follow-up of patients as well as a reference for genetic studies and treatment trials.